Key aspects of the study of psychophysiological adaptation of first-year students - Shevchenko, Svitlana (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2019)
The article considers and studies the problem of psychophysiological adaptation of freshmen through the concretization of the very concept of adaptation and determination of the time period of the adaptation period. Moreover, carried out a scientific analysis and experimental study of key aspects of psycho-physiological adaptation of first-year students. The levels of adaptive and communicative abilities, neuropsychic stability and moral norm, indicators of psychophysiological adaptation and the main features that indicate the sources of maladaptation have been determined. The criteria for psychophysiological adaptation (state of health, mood, anxiety, fatigue, activity behavior) are highlighted, and prospects for further research are formulated.According to the results of the work it was found that most freshmen have high rates of development of communicative abilities and moral normativity. They really assess their role in the team, in relationships, focusing on compliance with generally accepted norms of behavior. Freshmen are capable of accepting other people as they are, respect their originality and the right to be themselves. The development of such an ability characterizes them as a mature personality.High optimism score and high ability for somatic regulation were found. In addition, a moderate (average) level of psychophysiological maladaptation was found in young people. From time to time, they have certain difficulties associated with changes in the forms, teaching and assessment methods that are characteristic of a comprehensive school, and most often they experience problems due to a deterioration in well-being, namely, due to the characteristics of individual mental processes of freshmen, a decrease their overall activity and a decrease in motivation for any activity. Freshmen are dominated by a low level of development of adaptive abilities and neuropsychic stability.The data obtained indicate the need to develop a system of measures to update the adaptive capabilities of freshmen. We identified this direction as a promising vector for further studies of this problem.
Keywords: psychophysiological adaptation; signs of maladjustment; adaptive capabilities; first-year students